Evaluasi dan Analisis untuk Mengatasi Masalah Lost Circulation Dan Stuck Pipe Pada Sumur X - Rikumahu, Marcia Violetha; Geovanny Branchiny Imasuly (Jurnal Bhara Petro Energi, 2025)
Drilling operations do not always proceed smoothly as expected. Various issues can disrupt the drilling process and result in significant operational losses. Among the common problems encountered are lost circulation and stuck pipe incidents. Lost circulation often occurs in highly fractured formations, while stuck pipe events can lead to additional costs associated with non-productive time and fishing operations. In Well X, the causes of lost circulation and stuck pipe incidents were analyzed from several aspects, including drilling fluid properties, formation characteristics, hydrostatic pressure calculations, and pressure differentials. The analysis revealed that the primary cause of the stuck drill string was differential pressure resulting from excessive mud density, which caused the drill string to adhere to the formation wall. Additionally, the loss of drilling mud into the formation contributed to the problem, leading to financial losses, particularly in terms of drilling fluid costs. Both lost circulation and stuck pipe incidents can hinder well completion, ultimately increasing the drilling time and cost beyond initial projections. Therefore, a detailed investigation was conducted to determine the causes of these issues and assess the mitigation measures that had been implemented. In Well X, the stuck pipe problem was addressed using lost circulation materials (LCM) selected based on compatibility with the penetrated formation to optimize drilling operations. The evaluation focused on the drilling mud properties, including its rheology, as well as the drilling equipment used. These efforts were undertaken to ensure the continuation of drilling operations and the successful completion of the well.